The Nursing Community Apgar Questionnaire in Rural Australia: An evidence based approach to recruiting and retaining nurses - Molly Prengaman; Daniel R Terry; David Schmitz; Ed Baker (Rural Nurse Organization; Binghamton University, 2017)
Purpose: To date, the Nursing Community Apgar Questionnaire (NCAQ) has been effectivly utlized to quantify resources and capabilities of a rural Idaho communities to recruit and retain nurses. As such, the NCAQ was used in a rural Australian context to examine its efficacy as an evidence-based tool to better inform nursing recruitment and retention. Sample: The sample included nursing administrators, senior nurses and other nurses from six health facilities who were familiar with the community and knowledgeable with health facility recruitment and retention history. Participants were registered nurses and/or directly involved in nursing recruitment. Method: The 50 factor NCAQ was administered online. Data were cleaned, checked, and analyzed by assigning quantitative values to the four-point scale of community advantages or challenges for each factor and then weighted according to the participant's perceived importance to create a community asset and capability measure. Higher scores represented more developed community assets and capabilities relating to nursing recruitment and retention. Findings: The findings demonstrate that lifestyle, emphasis on patient safety and high quality care, availability of necessary materials and equipment, perception of quality were among the highest scoring factors and considered to have the most impact on recruiting and retaining nurses. The lowest factors impacting recruitment and retention included spousal satisfaction, access to larger communities, and opportunities for social networking within communities. Conclusions: The implementation of the NCAQ has the capacity to offer health facilities and managers to examine what is appealing about the health service and community, while highlighting key challenges impacting recruitment and retention. The NCAQ assists health services to develop strategic plans tailored specifically to enhance recruitment and retention of nursing staff. Its use has the capacity to provide health services with greater evidence as they seek to address site specific or regional recruitment and retention issues. Keywords:  Rural, nursing, Workforce, Recruitment, Retention, Community apgar DOI:  http://dx.doi.org/10.14574/ojrnhc.v17i2.459